1982
DOI: 10.1093/infdis/146.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Herpes Simplex Virus to Adenine Arabinoside and E-5-(2-Bromovinyl)-2′-Deoxyuridine: A Physical Analysis

Abstract: The physical map limits of DNA sequences within the DNA polymerase locus of herpes simplex virus (HSV) type 1 that define resistance mutations to adenine arabinoside (ara-A) and E-5-(2-bromovinyl)-2'-deoxyuridine (BVDU) were determined. Intertypic recombinants between HSV types 1 and 2, generated by marker rescue of temperature-sensitive mutations, had genome structures determined by restriction endonuclease analysis and were used to show that the resistance mutation for ara-Ar-1 is closely linked to the resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…60 ,uM for strain KOS (similar to that reported by Bastow et al [2]) and an ED50 about threefold higher for PAAr5. These ED50 values are different from those reported by another group for these two viruses (11) or from those values which can be abstracted from When the relative susceptibilities of KOS and PAAr5 to araA were examined in the presence of 3.5 ,uM DCF (the dose used by Bastow et al…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…60 ,uM for strain KOS (similar to that reported by Bastow et al [2]) and an ED50 about threefold higher for PAAr5. These ED50 values are different from those reported by another group for these two viruses (11) or from those values which can be abstracted from When the relative susceptibilities of KOS and PAAr5 to araA were examined in the presence of 3.5 ,uM DCF (the dose used by Bastow et al…”
mentioning
confidence: 56%
“…Nevertheless, there is considerable variation among HSV pol mutants with respect to araA resistance, even among those which are resistant to PAA or PFA or both. For example, PAAr5 has been reported to be more resistant to araA than are other araA-resistant mutants (8,11; this report), whereas other PAAr mutants have been reported to be sensitive to araA (6,8,16,17 The isolation of araA-resistant mutants (8,31) implies that araA acts selectively on HSV, and the mapping of resistance mutations to the pol locus implies that at least some of this selectivity resides in the HSV DNA polytnerase. One could hypothesize that the properties of the polymerase account for all of the selectivity.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Since their antiviral activity depends on the presence of specific viral enzymes, they cannot be broad-spectrum antiviral agents and act on viruses that belong to families phylogenetically distant. Viral mutants readily arise upon treatment with a given nucleoside analog (4). Therefore, more-selective inhibitors that block different steps of viral replication are needed (7).…”
mentioning
confidence: 99%
“…For example, the isolation of mutants resistant to arabinosyladenine (vidarabine [araA]) (6,9) demonstrated that, despite its cytotoxicity, araA is selective against HSV. Thus far, all araA resistance mutations have been mapped to the HSV DNA polymerase (pol) gene (2, 6,7,9), demonstrating that the polymerase is a target of araA and contributes to its selectivity.…”
mentioning
confidence: 99%